Kaon Femtoscopy with Lévy-Stable Sources from <semantics><msqrt>sNN</msqrt>=200</semantics> GeV <semantics>Au+Au</semantics> Collisions at RHIC - Ayon Mukherjee (Universe, 2023)
Femtoscopy has the capacity to probe the space-time geometry of the particle-emitting source in heavy-ion collisions. In particular, femtoscopy of like-sign kaon pairs may shed light on the origin of non-Gaussianity of the spatial emission probability density. The momentum correlations between like-sign kaon pairs are measured in data recorded by the STAR experiment, from <semantics><msqrt>sNN</msqrt>=200</semantics> GeV <semantics>Au+Au</semantics> collisions at RHIC, BNL. Preliminary results hint at the possible existence of non-Gaussian, Lévy-stable sources, with the likely presence of an anomalous diffusion process in the signal for the identically charged kaon pairs so produced. More statistically significant studies at lower centre-of-mass energies may contribute to the search for the critical end point of QCD.